ReAsH/tetracystein-based correlative light-electron microscopy for HIV-1 imaging during the early stages of infection. (6th July 2018) - Lysova, Iryna; Spiegelhalter, Coralie; Réal, Eleonore; Zgheib, Sarwat; Anton, Halina; Mély, Yves
Abstract: Visualization of viruses in the host cell during the course of infection by correlative light-electron microscopy (CLEM) requires a specific labelling of the viral structures in order to recognize the nanometric viral cores in the intracellular environment. For Human immunodeficiency virus type 1 (HIV-1), the labelling approaches developed for fluorescence microscopy are generally not suited for transmission electron microscopy (TEM), so that imaging of HIV-1 particles in infected cells by CLEM is not straightforward. Herein, we adapt the labeling approach with a tetracystein tag (TC) and a biarsenical resorufin-based label (ReAsH) for monitoring the HIV-1 particles during the early stages of HIV-1 infection by CLEM. In this approach, the ReAsH fluorophore triggers the photo-conversion of 3, 3-diaminobenzidine tetrahydrochloride (DAB), generating a precipitate sensitive to osmium tetroxide staining that can be visualized by transmission electron microscopy. The TC tag is fused to the nucleocapsid protein NCp7, a nucleic acid chaperone that binds to the viral genome. HeLa cells, infected by ReAsH-labeled pseudoviruses containg NCp7-TC proteins exhibit strong fluorescent cytoplasmic spots that overlap with dark precipitates in the TEM sections. The DAB precipitates corresponding to single viral cores are observed all over the cytoplasm, and notably near microtubules and nuclear pores. This work describes for the first time a specific contrast given by HIV-1 viral proteins in TEM images and opens new perspectives for the use of CLEM to monitor the intracellular traffic of viral complexes.